PENGARUH PERGERAKAN NILAI TUKAR DAN VOLUME TRANSAKSI TERHADAP PENDAPATAN TRANSAKSI DEVISA (STUDI KASUS PADA PT. BII, TBK KANTOR CABANG BOGOR) - Ramlan Ruvendi; Herdiah Kusweni (STIE Binaniaga, 2006)
Exchange or conversion rate is one of the important factors in an open economy since its big impact on the running transaction balance, foreign balance or other economical factors. Exchange rate plays a central role in international trade because exchange rate enables us to compare all products and services prices from other countries. The policy to predict and react on the exchange rate fluctuation is developing in line with the growing understanding of how the national and international monetary systems work. In addition transparency in accounting and taxation rules concerning the un/profitability from the exchange transactions and more familiar of economical effect of foreign currencies on cash flow and market value in the future. This research was carried out at PT. BII Ltd. Bogor Branch Office, and based on the problems, the purposes of the study were: (1) to know what factor that influence the movement of exchange rate (2) to see whether the movement and the volume of the exchange rate have significant relationship on the income from foreign exchange transactions (3) to identify if there is an influence of foreign exchange movement on the income from foreign exchange transactions and (4) to know is there an influence of transaction volume on the income from foreign exchange transactions. There were several factors that influence the foreign exchange rate on US Dollar, they are: (1) economical foundation (including inflation rate, BI interest rate, government control and income rate) (2) external factors (including American interest rate and policy, the rise of world crude oil price, European interest rate, American economic condition etc.) (3) market bias (including supply and demand, expectation and rumors). The influence of both foreign exchange rate (FER) and transaction volume (TV) analysis on the income of foreign exchange transactions (IFET) at PT. BII Ltd. Bogor Branch Office the writer found the regression equation as = -432050000.042 + 4762.800NT + 0.000595VT. The doubled regression linear of collected data gave a parameter value 4762.800NT and 0.000595VT and a constant value -432050000.042. The double correlation of the FER variable and the TV on the IFET at this company was positive and the coefficient correlation (r) was 0.577. The determinant coefficient (r squared) was 0.333 that means 33.30% of the IFET variety was caused by doubled regression between the IFET with FER and TV. The remaining 66.70% was explained by variables other than FER and TV that influence the IFET.